2013
DOI: 10.1074/jbc.m113.512665
|View full text |Cite
|
Sign up to set email alerts
|

Novel Key Metabolites Reveal Further Branching of the Roquefortine/Meleagrin Biosynthetic Pathway

Abstract: Background:The fungal roquefortine/meleagrin gene cluster is a source of diverse bioactive molecules. Results: Novel metabolites of the roquefortine/meleagrin biosynthetic pathway were discovered, and synthetase genes were assigned to biosynthetic reactions. Conclusion: Distinctive unspecificity of modifying enzymes leads to excessive branching in the pathway, resulting in various intermediates and products. Significance: Metabolites from the roquefortine/meleagrin gene cluster have potential antimicrobial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 21 publications
0
66
0
1
Order By: Relevance
“…Gene inactivation experiments revealed that the rearrangement reaction that forms the triazaspirocyclic skeleton proceeds via a nitrone intermediate, named roquefortine L ( 67 ). 204 Flavin-dependent monooxygenase RoqM was identified as the enzyme responsible for nitrone installation because ΔroqM mutants did not produce 70 and 71 , and instead accumulated 69 . Furthermore, gene inactivation of roqO , which encodes a predicted P450 monooxygenase, suggested that this enzyme could catalyze a requisite oxidation at C 16 on 67 to promote the rearrangement reaction to the triazaspirocycle ( 72 → 70 ).…”
Section: N–o Bond Forming Enzymesmentioning
confidence: 99%
“…Gene inactivation experiments revealed that the rearrangement reaction that forms the triazaspirocyclic skeleton proceeds via a nitrone intermediate, named roquefortine L ( 67 ). 204 Flavin-dependent monooxygenase RoqM was identified as the enzyme responsible for nitrone installation because ΔroqM mutants did not produce 70 and 71 , and instead accumulated 69 . Furthermore, gene inactivation of roqO , which encodes a predicted P450 monooxygenase, suggested that this enzyme could catalyze a requisite oxidation at C 16 on 67 to promote the rearrangement reaction to the triazaspirocycle ( 72 → 70 ).…”
Section: N–o Bond Forming Enzymesmentioning
confidence: 99%
“…22 More recently, a rigorous structural elucidation of the metabolites of this pathway prompted a revision of the biosynthetic mechanism for this particular rearrangement. 35 The key revision to this newly proposed metabolic pathway is the generation of the nitrone-bearing intermediate roquefortine L ( 7 ) by RoqM from 1 (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Fungi are particularly useful microorganisms in fermentation as they produce an array of diverse natural products, many of which have potential as therapeutic agents. Roquefortine C has been a compound of interest for a number of years due to its structural complexity and uniqueness (Shangguan et al, 2008) and also for its role as a biosynthetic precursor to a number of biologically active related metabolites (Ali et al, 2013; Garcia-Estrada et al, 2011; Han et al, 2013; Koizumi et al, 2004; Kosalkova et al, 2015; Reshetilova et al, 1995; Ries et al, 2013; Zheng et al, 2013). Using roquefortine C as a model compound, we have developed an experiment to introduce undergraduate students to the fields of fermentation and complex natural products.…”
Section: Introductionmentioning
confidence: 99%